Antibacterial Activity Test of Ceremai Leaf Ethanol Extract (Phyllanthus acidus (L.) Skeels) Against Bacteria Causing Skin Infections by KLT-Bioautography and Agar Diffusion - Naid, Tadjuddin; Herwin, Herwin; Muldin, Nurul Insani (Fakultas Farmasi, Universitas Muslim Indonesia, 2025)
Ceremai leaves (Phyllanthus acidus) are known for their medicinal properties, including the treatment of infectious diseases. This study aims to evaluate the antibacterial activity of ethanol extract from Ceremai leaves against skin infection-causing bacteria using Thin Layer Chromatography-Bioautography (TLC-Bioautography) and agar diffusion methods. The study began with an antibacterial screening test, followed by TLC-Bioautography, and then determination of the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) at various concentrations (0.125% to 16%). The agar diffusion method was used to further assess antibacterial activity. Screening results showed antibacterial activity at a concentration of 1%. TLC-Bioautography with a chloroform: methanol: water (20:2:0.5) eluent revealed active spots with Rf values of 0.8, 0.54, 0.36, and 0.29. The MIC values were 0.25% for P. acnes and S. aureus, and 0.5% for P. aeruginosa and S. epidermidis. The MBC values were 0.5% for P. acnes and S. aureus, and 1% for P. aeruginosa and S. epidermidis. The largest inhibition zone in the agar diffusion test was observed at a 32% concentration against S. aureus, measuring 20.11 mm. These findings suggest that Ceremai leaf extract has significant antibacterial potential and could be considered for developing alternative treatments for skin infections.